SISTEM DAILY REVENUE OF SALES UNTUK EFISIENSI DAN EFEKTIVITAS TENAGA KERJA DI TASIK RIA RESORT & SPA - Sendow, Jelly (Jurnal Hospitaliti, 2024)
System of daily revenue of sales is representing a set of report from daily revenue which must be made to know the hotel income as well as guest stayed percentage/occupancy in Tasik Ria Resort & SPA. This system depict how to streamline the night auditor without having to enhance its office hours. Intrinsically system of daily revenue of sales intended to maximize the role of the night auditor by streamlining result of job and also employee efficiency. As for such with the labor efficiency that is one of position in Accounting Departement namely Income Auditor can be eliminated because its duty is enforceable by Night Auditor. The real of studied more curcimstantial both of position its duty much the same to and even cage can overlap.